Five recurrent BRCA1/2 mutations are responsible for cancer predisposition in the majority of Slovenian breast cancer families - Novakovic Srdjan; Hocevar Marko; Besic Nikola; Goelen Guido; Zgajnar Janez; Teugels Erik; Krajc Mateja; De Grève Jacques (BMC, 2008)
Abstract Background Both recurrent and population specific mutations have been found in different areas of the world and more specifically in ethnically defined or isolated populations. The population of Slovenia has over several centuries undergone limited mixing with surrounding populations. The current study was aimed at establishing the mutation spectrum of BRCA1/2 in the Slovenian breast/ovarian cancer families taking advantage of a complete cancer registration database. A second objective was to determine the cancer phenotype of these families. Methods The original population database was composed of cancer patients from the Institute of Oncology Ljubljana in Slovenia which also includes current follow-up status on these patients. The inclusion criteria for the BRCA1/2 screening were: (i) probands with at least two first degree relatives with breast and ovarian cancer; (ii) probands with only two first degree relatives of breast cancer where one must be diagnosed less than 50 years of age; and (iii) individual patients with breast and ovarian cancer, bilateral breast cancer, breast cancer diagnosed before the age of 40 and male breast cancer without any other cancer in the family. Results Probands from 150 different families met the inclusion criteria for mutation analysis of which 145 consented to testing. A BRCA1/2 mutation was found in 56 (39%). Two novel large deletions covering consecutive exons of BRCA1 were found. Five highly recurrent specific mutations were identified (1806C>T, 300T>G, 300T>A, 5382insC in the BRCA1 gene and IVS16-2A>G in the BRCA2 gene). The IVS16-2A>G in the BRCA2 gene appears to be a unique founder mutation in the Slovenian population. A practical implication is that only 4 PCR fragments can be used in a first screen and reveal the cancer predisposing mutation in 67% of the BRCA1/2 positive families. We also observed an exceptionally high frequency of 4 different pathogenic missense mutations, all affecting one of the cryptic cysteine residues of the BRCA1 Ring Finger domain. Conclusion A high mutation detection rate and the frequent occurrence of a limited array of recurring mutations facilitate BRCA1/2 mutation screening in Slovenian families.